Women's empowerment and the use of antenatal care services in Southeast Asian countries - Sebayang, Susy K.; Efendi, Ferry; Astutik, Erni (DHS Working Papers No. 129, 2017)
This study assessed the relationship between women’s empowerment and the use of antenatal care (ANC) services in five Southeast Asian (ASEAN) countries. The data used in the study are from the most recent Demographic and Health Surveys (DHS) conducted in Cambodia (2014), Indonesia (2012), Myanmar (2016), the Philippines (2013), and Timor-Leste (2009). The focus of the analysis was on currently married women who gave birth within the last 5 years before the survey. The two main outcomes were the number of ANC visits they made (four or more compared with none to three), and the timing of the first ANC visit (within the first trimester or later in the pregnancy). Four composite women’s empowerment variables were created from 17 indicators: (1) labor force participation; (2) disagreement with reasons for wife beating; (3) decision-making power over household issues; and (4) knowledge level (based on education and media exposure). Analysis used logistic regression with adjustment for complex sampling design. Overall, results differed among the five countries. Labor force participation was significantly associated with number of ANC visits in Cambodia, Philippines, and Timor- Leste. Disagreement with reasons for wife beating and women’s knowledge level were each independently associated with number of ANC visits in Cambodia, Indonesia, and Myanmar. Women’s decision-making power was associated with number of ANC visits in Cambodia and Indonesia. The association of women’s empowerment variables with timing of the first ANC visit was not as evident as the association with number of visits. Labor force participation was significantly associated with attending ANC in the first trimester in Cambodia and Philippines. Disagreement with reasons for wife beating was significantly associated with early ANC visit only in Timor-Leste. Women’s knowledge level was associated with early first ANC visit only in Cambodia, and women’s decision-making power was associated with early first ANC visit only in Philippines. There was no difference between adult and adolescent mothers in the association between women’s empowerment and use of ANC, except in two cases. In Cambodia, adolescent mothers with medium knowledge had lower odds of attending four or more ANC visits compared with adult mothers with poor knowledge; and in Myanmar, adolescent mothers with high labor force participation had higher odds of attending the first ANC visit early compared with the reference group of adult mothers with low labor force participation.
For assistance using downloaded citations from The DHS Program, please visit http://dhsprogram.com/publications/Citing-DHS-Publications.cfm
The DHS Working Papers series is a prepublication series of papers reporting on research in progress that is based on Demographic and Health Surveys (DHS) data. This research is carried out with support provided by the United States Agency for International Development (USAID) through The DHS Program (#AID-OAA-C-13- 00095). The views expressed are those of the authors and do not necessarily reflect the views of USAID or the United States Government.